37.6k views
5 votes
What is 5x + 2 = -6x - (-3)

2 Answers

1 vote

Answer:

x=1/11

Explanation:

User SoySolisCarlos
by
6.5k points
3 votes

Answer:

x = 1/11

Explanation:

Step 1: Write equation

5x + 2 = -6x - (-3)

Step 2: Solve for x

Simplify: 5x + 2 = -6x + 3

Add 6x to both sides: 11x + 2 = 3

Subtract 2 on both sides: 11x = 1

Divide both sides by 11: x = 1/11

Step 3: Check

Plug in x to verify it's a solution.

5(1/11) + 2 = -6(1/11) - (-3)

5/11 + 2 = -6/11 + 3

27/11 = 27/11

User Michael Laffargue
by
5.5k points